PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 49 TAMERAN KECAMATAN BENGKALIS KABUPATEN BENGKALIS - ', Munir; ', Syahrilfuddin; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is the weaknees of student’s learning result of sains subject. It show from 24 student’s, 14 students (58,33%) have lower score, and it only 10 student’s (41,66%) have average score 63. The KKM of this school is 70. According to that problem, the research by implementing cooperative learning model type group investigation. In cycle I, the percentage of teachers activity in first meeting is adguate 58,33%. In second meeting, teachers activity significatly increased to 66,66% with good category. In cycle 2, firts meeting was a very good category 83,33% and second meeting indicated a very good category 91,66%. Meanwhile, the activityof student’s also imvroved. In cycle I indicated 54,16% in adequatecategory and in cycle 2 has increased up to 62,50% with good category. In cyle 2, first meeting, the activity of student’s has been increasing to 75% with goog category and second meeting indicated very good category 87,50%. An average score of student’s 63 it increased to 70,83 in cycle I, and 76,25 in cycle 2. In classical completeness, cycle 1 and cycle 2 achieved. In conclussion, implementatation cooperative learning model group investigation teacin can improve student’s learning result of five grade students of SD Negeri 49 Tameran Kecamatan Bengkalis Kabupaten Bengkalis in sains subject. Key word: Cooperative model type group investigation, learning result of sains subject